Eponychial Flap: A Simpler Way to Achieve Better Aesthetic Outcome in a Fingertip Amputation - Samantaray, Srikant Aruna; Kalathingal, Kader; Muhammed, Hafiz; Joseph, Subin (Indian Journal of Plastic Surgery, 2022)
Background There are numerous flaps described for the treatment of fingertip amputation. Shortened nail length resulting from amputation is an ignored area. Eponychial flap is a simple procedure that helps to lengthen the nail plate and correct this deformity.Methods This case–control study was conducted between April 2016 and June 2020 aimed at comparing the outcome of nail defects in a fingertip amputation treated with eponychial flap and those treated without an eponychial flap.Results Among 165 patients treated for fingertip injury, 78 were treated with eponychial flap (group A) and 87 without eponychial flap (group B). In group A, the nail length was 72.54% (standard deviation [SD]: 14.4) and the nail plate area was 74.35% (SD: 13.96) compared with the contralateral uninjured nail. These results were significantly better (p = 0.000) compared with group B where the values were 36.49 (SD: 8.45) and 35.8% (SD: 8.4), respectively. The aesthetic outcome score was also significantly higher in group A patients (p = 0.002). The patient satisfaction was superior in group A compared with group B.Conclusion The eponychial flap is a simple and reliable technique that can be used to restore the visible nail length in traumatic fingertip defects. Compared with fingers treated without nail lengthening with eponychial flap gives excellent aesthetic results.
Keywords: fingertip amputation; eponychial flap; fingertip injury